Egeo - an advanced course for students of geography Book 2 - Lam Thi Hoa Binh (Hà Nội Đại học sư phạm, 2009)
Landform; Land and soil; Trees and forests; Ecotourism; Climate & climate effects; Pollution; Groundwater; Energy; Mapping.
Keywords: Geography -- Study and teaching; Địa lý; Dạy địa lí